2004
DOI: 10.3310/hta8100
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and economic evaluation of magnetic resonance cholangiopancreatography compared with diagnostic endoscopic retrograde cholangiopancreatography

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 66 publications
3
57
1
5
Order By: Relevance
“…Gallstones can be documented within the common bile duct with accuracy similar to ERCP by EUS (39,205,(207)(208)(209)(210)(211)(212)(213)(214)(215)(216)(217)(218)(219)(220)(221)(222)(223)(224)(225)(226), with somewhat lower accuracy by MRCP (227)(228)(229)(230)(231)(232)(233), and by intraoperative cholangiography at the time of laparoscopic cholecystectomy (234)(235)(236)(237). Identification of a biliary etiology of acute pancreatitis is important because recurrent episodes will occur in one-third to two-thirds of these patients in follow-up periods of as short as 3 months unless gallstones are eliminated (238,239).…”
Section: Treatment Guideline Vii: Role Of Ercp and Biliary Sphincteromentioning
confidence: 99%
See 1 more Smart Citation
“…Gallstones can be documented within the common bile duct with accuracy similar to ERCP by EUS (39,205,(207)(208)(209)(210)(211)(212)(213)(214)(215)(216)(217)(218)(219)(220)(221)(222)(223)(224)(225)(226), with somewhat lower accuracy by MRCP (227)(228)(229)(230)(231)(232)(233), and by intraoperative cholangiography at the time of laparoscopic cholecystectomy (234)(235)(236)(237). Identification of a biliary etiology of acute pancreatitis is important because recurrent episodes will occur in one-third to two-thirds of these patients in follow-up periods of as short as 3 months unless gallstones are eliminated (238,239).…”
Section: Treatment Guideline Vii: Role Of Ercp and Biliary Sphincteromentioning
confidence: 99%
“…In clinical practice, if there is intermediate concern regarding the possibility of a retained common bile duct stone, and the patient is not felt to be a good candidate for cholecystectomy with cholangiogram within the near future, EUS or MRCP can be performed to assess for presence of bile duct stones and determine need for ERCP. EUS is generally considered to be the most accurate method to detect bile duct stones; sensitivity of MRCP for small bile duct stones is lower, especially for those that are impacted at the ampulla (229,230). EUS or MRCP are also useful to determine need for ERCP in patients who are pregnant, or in whom ERCP would be high risk or technically difficult due to reasons such as severe coagulopathy or altered surgical anatomy.…”
Section: Treatment Guideline Vii: Role Of Ercp and Biliary Sphincteromentioning
confidence: 99%
“…MRCP and diagnostic ERCP were compared for cost effectiveness through a literature scan over 28 articles by Kaltenthaler et al, and it was decided that MRCP was more economical [12]. In our study, it was determined that the cost of one MRCP event cost TL 65, while one ERCP event cost approximately TL 284.…”
Section: Discussionmentioning
confidence: 89%
“…The sensitivity for strictures was 100.0% and specificity ranged from 98.0% to 99.0%. It was concluded that although there are some findings suggesting that MRCP is a sensitive method compared with diagnostic ERCP, the obtained values for malignancy compared with choledocholithiasis were somewhat lower 13 . In the present study, the sensitivity, specificity, and positive and negative predictive values of MRCP in detecting common bile duct dilatation were 70.0%, 77.2%, 73.6%, and 73.9%, respectively.…”
Section: Methodsmentioning
confidence: 92%